An Analysis of Students’ Anxiety in Learning English At The Fourth Semester Students of Midwifery Department in Aufa Royhan University: Analysis of Students’ Anxiety in Learning English At The Fourth Semester Students of Midwifery Department in Aufa Royhan University - handayani, fitri rahma; nurdin, hidayanti rohimah; Juliana, Juliana; siregar, Sarmila hafni; Nasution, Nurlaila (Universitas Aufa Royhan, 2023)
English is the most widely used language in the world. As a result, it is crucial for students to learn English. To do it, someone must not have anxiety towards it. word